Exceptional People : How Migration Shaped Our World and Will Define Our Future - Goldin, Ian, 1955- (Book collections on Project MUSE., 2011)
"Throughout history, migrants have fueled the engine of human progress. Their movement has sparked innovation, spread ideas, relieved poverty, and laid the foundations for a global economy. In a world more interconnected than ever before, the number of people with the means and motivation to migrate will only increase. Exceptional People looks at the profound advantages that such dynamics will have for countries and migrants the world over. Challenging the received wisdom that a dramatic growth in migration is undesirable, the book proposes new approaches for governance that will embrace this international mobility. The authors explore the critical role of human migration since humans first departed Africa some fifty thousand years ago -- how the circulation of ideas and technologies has benefited communities and how the movement of people across oceans and continents has fueled economies. They show that migrants in today's world connect markets, fill labor gaps, and enrich social diversity. Migration also allows individuals to escape destitution, human rights abuses, and repressive regimes. However, the authors indicate that most current migration policies are based on misconceptions and fears about migration's long-term contributions and social dynamics. Future policies, for good or ill, will dramatically determine whether societies can effectively reap migration's opportunities while managing the risks of the twenty-first century. A guide to vigorous debate and action, Exceptional People charts the past and present of international migration and makes practical recommendations that will allow everyone to benefit from its unstoppable future growth"--Provided by publisher.